Cuttlefish color change as an emerging proxy for ecotoxicology - Gouveneaux, Anaïd; Minet, Antoine; Jozet-Alves, Christelle; Knigge, Thomas; Bustamante, Paco; Lacoue-Labarthe, Thomas; Bellanger, Cécile (Frontiers in Physiology, 2023)
Lately, behavioral ecotoxicology has flourished because of increasing standardization of analyses of endpoints like movement. However, research tends to focus on a few model species, which limits possibilities of extrapolating and predicting toxicological effects and adverse outcomes at the population and ecosystem level. In this regard, it is recommended to assess critical species-specific behavioral responses in taxa playing key roles in trophic food webs, such as cephalopods. These latter, known as masters of camouflage, display rapid physiological color changes to conceal themselves and adapt to their surrounding environments. The efficiency of this process depends on visual abilities and acuity, information processing, and control of chromatophores dynamics through nervous and hormonal regulation with which many contaminants can interfere. Therefore, the quantitative measurement of color change in cephalopod species could be developed as a powerful endpoint for toxicological risk assessment. Based on a wide body of research having assessed the effect of various environmental stressors (pharmaceutical residues, metals, carbon dioxide, anti-fouling agents) on the camouflage abilities of juvenile common cuttlefish, we discuss the relevance of this species as a toxicological model and address the challenge of color change quantification and standardization through a comparative review of the available measurement techniques.